2019
DOI: 10.1039/c9ay00383e
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical detection of oxacillin resistance with SimpleStat: a low cost integrated potentiostat and sensor platform

Abstract: Testing outside the laboratory environment, such as point of care testing, is a rapidly evolving area with advances in the integration of sample handling, measurement and sensing elements widely reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…Electrochemical DNA biosensors represent an exciting approach to the fast, low-cost detection of clinically important biomarkers [9,10] at the point of care [11]. A range of electrode materials and electrochemical measurement approaches have been employed for sensitive measurements (cyclic voltammetry [12], differential pulse voltammetry [13], square wave voltammetry [14] and electrochemical impedance spectroscopy [15]).…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical DNA biosensors represent an exciting approach to the fast, low-cost detection of clinically important biomarkers [9,10] at the point of care [11]. A range of electrode materials and electrochemical measurement approaches have been employed for sensitive measurements (cyclic voltammetry [12], differential pulse voltammetry [13], square wave voltammetry [14] and electrochemical impedance spectroscopy [15]).…”
Section: Introductionmentioning
confidence: 99%
“…For macroscale electrodes functionalised with biological molecules, such as DNA or antibodies, the expectation is that differential pulse voltametric peak currents will reduce upon target hybridisation. It has been observed that these effects can be reversed when micro- or nanoscale electrodes are employed [ 20 , 46 ], but for this study, the electrodes used were comfortably on the macro scale (diameter = 2.95 mm). For nanomolar (>10 nM) and micromolar concentrations, an increase in the peak current following hybridisation was consistently observed (and has also been observed in other data from our lab involving SPCEs) [ 1 ] for carbon electrodes which is likely explained by the high surface density of hybridised DNA amplicons changing the interfacial properties of the electrode and, therefore, altering the electrochemical response.…”
Section: Resultsmentioning
confidence: 99%
“…For macroscale electrodes functionalised with biological molecules, such as DNA or antibodies, the expectation is that differential pulse voltametric peak currents will reduce upon target hybridisation. It has been observed that these effects can be reversed when microor nanoscale electrodes are employed [20,46], but for this study, the electrodes used were…”
Section: Dna Sensor Hybridisation Specificitymentioning
confidence: 98%
See 1 more Smart Citation
“…Recent advances in potentiostat production have made potentiostats available which are small, do-it-yourself, portable and cheap allowing for greater access for fabrication techniques [31][32][33][34]. This review will discuss some of the challenges that are shared between electrochemical hydrogel fabrication methods and how these have been addressed.…”
Section: Introductionmentioning
confidence: 99%